2017
DOI: 10.3329/bmrcb.v42i2.31998
|View full text |Cite
|
Sign up to set email alerts
|

Quitting Attempts in Bangladeshi Male Rural Smokers and Social Correlates

Abstract: Smokers lose, on average, about ten years of life, while smokers who quit before age of 35 years have mortality rates similar to those who never smoked. There is lack of support for smokers in their quitting attempt as well as empirical data to design support strategies. This cross sectional study was conducted in 2012 in rural Tangail, to identify the smoking quitting attempts and its correlates in Bangladeshi population. A total of 505 adult rural smokers were enlisted, and interviewed using a pretested ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several previous studies determined the correlates of attempts to quit smoking and smoking habit in Bangladesh. Flora, Kabir, and Moni (2017) identified the social correlates of intention to quit and quitting attempt of smoking in Bangladesh by gender and place of residence ( Flora et al, 2017 ). This study found that intention to quit smoking was influenced by education, age at starting smoking, type of smokers and number of smoker friends and attempt to quit smoking associated with type of smokers and number of smoker friends.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies determined the correlates of attempts to quit smoking and smoking habit in Bangladesh. Flora, Kabir, and Moni (2017) identified the social correlates of intention to quit and quitting attempt of smoking in Bangladesh by gender and place of residence ( Flora et al, 2017 ). This study found that intention to quit smoking was influenced by education, age at starting smoking, type of smokers and number of smoker friends and attempt to quit smoking associated with type of smokers and number of smoker friends.…”
Section: Introductionmentioning
confidence: 99%